2019
DOI: 10.1007/s40090-019-0179-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of Senecio anteuphorbium as green corrosion inhibitor for S300 steel

Abstract: The present work proposes the study of the extract of Senecio anteuphorbium (SA) as green corrosion inhibitor. This inhibitory effect of SA extract on the corrosion of S300 steel in hydrochloric acid 1 M has been evaluated by using the potentiodynamic polarization and electrochemical impedance spectroscopy. From the outcome of the polarization curves, SA extract acts as mixed-type inhibitor. The inhibition efficiency increased with the extract concentration increase to achieve a maximum of 91% at 30 mg/L. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…The juice of S anteuphorbium is commonly used by populations of some areas in order to treat rheumatism and burns pain 25 . A recent study has shown its usage as a green corrosion inhibitor for S300 steel 26 . However, the Senecio genus is a source of pyrrolizidine alkaloids; it is the most common poisonous component and can therefore cause hepatotoxicity and carcinogenesis 27 .…”
Section: Introductionmentioning
confidence: 99%
“…The juice of S anteuphorbium is commonly used by populations of some areas in order to treat rheumatism and burns pain 25 . A recent study has shown its usage as a green corrosion inhibitor for S300 steel 26 . However, the Senecio genus is a source of pyrrolizidine alkaloids; it is the most common poisonous component and can therefore cause hepatotoxicity and carcinogenesis 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Chemisorption is one that has been listed by many authors. Several studies, for example, Chaudhari and Patel [80], Salinas-Solano et al [81], and Idouhli et al [82], have concluded that chemisorption forms a strong interaction between the metal and inhibitors, as shown in Figure 7. Thus, a film is formed on top of the metal surface.…”
Section: Inhibition Mechanismmentioning
confidence: 98%
“…On the other hand, chemisorption happens when the value of ∆G 0 ads is less than −40 kJ/mol. Idouhli et al [82] explained that chemisorption involves the sharing of molecules of the inhibitors with the metal surfaces. Chemisorption is a stronger type of adsorption compared to physisorption.…”
Section: Inhibition Mechanismmentioning
confidence: 99%
“…Moreover, the corrosion potential (Ecorr) is slightly shifted than the blank (≈15-77 mV), as described in Table 9. In general, an inhibitor is classified as an anodic or a cathodic type if the displacement in corrosion potential (Ecorr) values against the blank is larger than 85 mV 45,46 . In the present study, Ecorr shifted within 85 mV, suggesting the mixed type inhibitor.…”
Section: Homo-lumo Analysismentioning
confidence: 99%